Foetal loss and feminine sex ratios at birth in sub-Saharan Africa. (4th May 2021) - Morse, Anne; Luke, Nancy
Abstract : A wealth of demographic research has explored the determinants of sex ratios at birth, but few studies have considered the role of foetal loss (spontaneous abortion), in producing feminine sex ratios. One challenge is measuring the occurrence of foetal loss, which is difficult to recognize and report in survey research. This study uses the length of the birth interval as a proxy for foetal loss; foetal loss restarts the clock on time to conception and lengthens the birth interval. We use Demographic and Health Survey data on second births to women in 17 sub-Saharan African countries. Results show that longer second birth intervals are significantly related to lower odds of a male second birth and to feminine sex ratios at birth. These findings suggest that high levels of foetal loss, which could signal underlying poor maternal health in a population, have dramatic effects on the sex ratio at birth.